The Impact of Social Capital on Household Welfare in Indonesia Using the Propensity Score Matching Method - Mohtar Rasyid; Vinda Yulinda (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study aims to analyze the impact of social capital on household welfare in Indonesia. Social capital is considered an important asset that contributes to improving the economic and social welfare of households, but access to and utilization of social capital is not always evenly distributed among different groups in society. This study uses the Propensity Score Matching (PSM) method with the Average Treatment Effect on the Treated (ATT) approach and stratification techniques to estimate the influence of various social capital indicators on household welfare. The estimation results show that social capital has a positive and significant effect on household welfare, particularly through participation in social gatherings, membership in cooperatives, religious activities, neighbourhood security, social gatherings, women's activities, and childcare. However, some forms of social capital that are communal in nature and related to basic services do not show a significant difference in household welfare. These findings confirm that strengthening social capital plays an important role in improving household welfare in Indonesia